Evaluation of Heavy Metal Pollutants From Plateau Mines in Wetland Surface Deposits - Yu, Li; Kaiyi, Shi; Jie, Yuan; Qiyu, Kuang (Frontiers in Environmental Science, 2021)
The Liupanshui Minghu Wetland is a typical artificial urban wetland in a plateau mining region. It is important to identify the sources and potential ecological risks of heavy metal contaminants in its surface sediments to monitor the wetland and the downstream water quality and prevent pollution. In this study, we measured the concentrations of six toxic heavy metals (Pb, Zn, Cr, Cu, Ni, and Cd) in the surface sediments collected from the Liupanshui Minghu Wetland. Further, the geological accumulation indices of heavy metals and their potential ecological risk indices, pollution levels, and associated ecological hazards were evaluated. The average levels of Pb, Zn, Cr, Cu, Ni, and Cd in the superficial sediments were 197, 222, 79.0, 59.1, 68.6, 4.67 mg/kg, respectively. With the exception of Cr, the concentrations of the remaining metals were greater than the background levels in the region. The Statistical analysis indicated a strong correlation between Pb, Zn, Cr, and Cu (p < 0.01). The pollution in the wetland by these elements can be attributed to human activities such as transportation, industrial activity, and agricultural production. Ni and Cd pollution can be attributed to human activities, such as coal mining, and natural phenomena, such as the weathering of mountains and rocks. The geological accumulation indices of Zn, Ni, and Cu indicated low levels of accumulation and minimal contamination. Cd and Pb were moderately enriched, and the levels of Cd and Pb contamination ranged from moderate to high. The potential ecological risk to the Shiyuan region (S) was the highest among the three regions in the wetland park. It was followed by the Longtoutan (L) region, and the potential ecological risk was the lowest in the Erdaoba (E) region. Among the six heavy metals, Cd was the main contributor to pollution in the Minghu Wetland. This study also strives to provide theoretical basis and data support for the prevention and control of heavy metal pollution in artificial wetlands in Alpine mining areas.